Do que dá pra rir, dá pra chorar : o padrão representacional das personagens LGBTAs das sitcoms originais Netflix na década de 2010 - Reis, Kaippe Arnon Silva (2022)
On its institutional YouTube channel, Netflix claims to be an ally of minority groups, including LGBTAs. This positioning leaded us to study the way these sexual identities are represented on the streaming TV shows. Thus, we analyze Netflix's sitcoms and, further, we seek to understand whether the humor on these shows serves the LGBTA community in a progressive, reactionary or neutral way. As a research object, we selected 88 episodes from nine Netflix original sitcoms released in the 2010s, and the sample episodes were selected based on the IMDb rating notes. The Content Analysis proposed by Bardin (2011) was used in a quantitative/qualitative approach through analytical categories developed from the theoretical propositions of Greimas (1973), Propp (1992) and Colling (2012), as well as the theoretical framework of Cultural Studies, Queer Studies and Gender Studies. As the result, we found out that the representation of the LGBTA community characters on the platform are potentially conservative because the demography of the researched object is: 52.5% are gays, 60% are male and 70% are represented by white people, showing us the struggle that a lot of people has on recognizing themselves on screen. We found out that there is a lack representation of different identities like intergender people, fluid and pansexual sexuality, polyamorous relationships, as well as identities that start from a non-Eurocentric logic, such as Brazilian travestis, people with two-spirit, identfitied in the native American peoples, or the third gender Hijra, from Indian culture. This research found a partial modification on the way this community appeared in TV shows throughout history, considering the delimitation of the corpus. In the series humor, we found 67 comic situations in the reactionary field, divided into the categories: "Limitation of identity to sexual practice", "Inferiorization reinforcement of deviant identities", "Reinforcement of gender and sexuality stereotypes”, “The search for homosexuality´s nature” and “Reinforcement of heteronormativity”; 42 comic situations were also located in a supposed neutrality; 40 situations in the progressive field, divided into the categories “Hierarchy of sexualities and gender conditions rethinking”, “The normality of an identity is a social construction”, “Binarism is a construction”, “Respect for those who want to be on the margins”, “Politicization of the abject” and “Problematization of heteronormativity”. Two comic situations that have both, reactionary and progressive content, were also found and we placed them in the “dubious” category. We note that the message sent by the humor scenes is not always coherent with the narrative. There are shows that emerge progressive discourses and dare the social structure, but sometimes, those shows also make reactionary jokes. In some sitcoms, for example, we found validation and diffusion of several inherent stereotypes, such as the innate demasculinization of gays. We conclude that to combat reactionary representations, the progressive representations must be created and exposed as round characters/identities, developing the characters beyond occasional participations which sometimes reinforce laughable stereotypes for the audience.